Increased medication costs for filaggrin‐related eczema and asthma. (1st September 2018) - Soares, P.; Fidler, K.; Felton, J.; Tavendale, R.; Hövels, A.; Bremner, S.A.; Palmer, C.N.A.; Mukhopadhyay, S.
Summary: Eczema and asthma are common chronic diseases. Eczema affects 15‐20% of schoolchildren and 2‐10% of adults while asthma affects 16‐18% of the UK population. Almost three‐quarters of children with early onset eczema, a severe and persistent form of eczema, will develop asthma in later life. The filaggrin gene helps produce a protein that creates a protective barrier on the skin against the entry of outside substances that trigger allergies. About 1 in 10 people carry a change in the filaggrin gene and this results in the production of defective protein that can no longer help maintain this skin barrier. This UK study aimed to find whether filaggrin mutations were associated with increased prescribing of medication for eczema and asthma and /or an increased number of asthma exacerbations (i.e. worsening) and whether this translated into different healthcare costs. The study shows that children with eczema and asthma carrying this gene change have substantially increased needs for both eczema and asthma medication through most of their childhood. Children with asthma carrying the gene change were also more prone to suffer asthma attacks over a nine‐year period, enhancing both hospital and human costs of the disease. It follows that a simple 'spit' gene test, that can be done anytime in life, including at birth or early childhood, could help predict long‐term healthcare costs and the long‐term risk of more severe disease for individuals with common chronic conditions such as eczema and asthma. Children and adults with filaggrin gene mutations may benefit from targeted treatment regimes, such as daily use of emollients from birth, which could lead to cost savings for healthcare systems and improvements in disease control and quality‐of‐life.